Comprehensive functional annotation of ESR1-driven enhancers in breast cancer reveals hierarchical activity independent of genomic and epigenomic contexts - Zekri, Yanis; Gregoricchio, Sebastian; Yapıcı, Elif; Huang, Chia-Chi Flora; Morova, Tunç; Altıntaş, Umut Berkay; Korkmaz, Gozde; Lack, Nathan A.; Zwart, Wilbert (Genome Research, 2025)
Estrogen receptor 1 (ESR1; also known as ERα, encoded by ESR1 gene) is the driving transcription factor in breast cancer development and progression. ESR1 genomic action is thought to operate under tight epigenetic control, with its chromatin binding and subsequent transcriptional output heavily reliant on the pioneer transcription factor FOXA1, which renders chromatin accessible for ESR1 binding. However, the exact contribution of the epigenome to selective enhancer activation by ESR1 remains to be fully elucidated. To address this, we employ a massively parallel reporter assay to profile 7576 individual ESR1 binding sites for hormone responsiveness. Only a minority of ESR1-occupied enhancers exhibit hormone-induced activity. These findings are confirmed by genomic data in situ, indicating that enhancer activation within a chromatinized context is robustly captured in a plasmid-based reporter assay. In silico integration of our findings with publicly available functional genomics data sets from breast cancer cell lines and tumor samples reveal distinct transcription complex compositions, 3D genome contexts, and regulatory dynamics associated with different classes of ESR1 binding sites. Overall, our results establish a comprehensive framework to highlight and elucidate the molecular basis underlying ESR1 genomic heterogeneity and its contribution to breast cancer biology and clinical outcomes.
10.1101/gr.280320.124